(untitled) (Research, Society and Development, 2025)
The use of cannabis as a medicinal treatment dates back to the firsts civilizations that used it in several deseases.. Currently, cannabis is used in the treatment of several neurodegenerative diseases, such as Alzheimer’s disease and it´s therapeutic use. To assess if whether patients affected by Alzheimer’s disease are able to notice improvements in the symptoms of the disease after starting treatment with cannabis-based medication. This is an observational cross-sectional study carried out with a quantitative approach. The results revealed that 58.8% of the participants were male, and it also covered several age groups, with emphasis on ages between 50 and 85 years. Among the participants, 29.9% were widowed and 58% had been through University Education. Approximately 58.8% of the participants used cannabis-based medication less than a year ago, under medical prescription and in conjunction with other medications. The main benefits reported by participants were improvements in memory and appetite, followed by improvement in concentration and sleep. These results suggest a systemic effect of cannabis-based drugs on the body, with emphasis on improvements in memory and appetite. It is important to highlight that in 76.5% of cases, cannabis therapy was performed in conjunction with conventional treatments. Research on the therapeutic effects of cannabis is at an early stage, but it shows promising results in the treatment of conditions such as Alzheimer’s Disease. Cannabis therapy has been shown to be safe and effective, especially when combined with traditional treatments. In addition, it is important to emphasize that the use of these drugs should ideally be prescribed by experienced professionals, taking into account the individual benefits and risks of each patient. The use of cannabidiol as a complementary therapy shows promise, but more accessibility to the cost of drugs and more research is still needed so that more people can effectively benefit from these resources.